E-Penggalangan Dana Untuk Penderita Kanker di Kota Medan Menggunakan Metode Crowdfunding dan Framework Bootstrap - Adjie Surya Ananda Siregar; Tantri Hidayati Sinaga; Eka Rahayu (Query: Journal of Information Systems, 2023)
Cancer is a non-communicable disease that is the second largest cause of death. Globally, about 1 in 6 deaths are due to cancer. About 70 percent of cancer deaths occur in low and middle-income countries. One of the problems faced by cancer sufferers is the financial factor. Because the treatment or surgery on cancer requires costly costs. The government has made various efforts to help reduce costs, but not everyone gets it. The method in this study is the crowdfunding model that will be used is Donation-Based Crowdfunding, this model is no different from alms/donation. This system will be tested using the ISO 25010 method. The result of this research is that this fundraising system can help people living with cancer in the field to pay for treatment and make it easier for donors to distribute their aid.Keywords: Cancer, Fundraising, Crowdfunding, Donation Based ISO 25010